Process development of silica extraction from RHA: a cradle to gate environmental impact approach - Joglekar, Saurabh N.; Kharkar, Rhushikesh A.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2019)
India is one of the major rice-producing countries. Rice husk is a major agricultural by-product from rice production, which is used as a fuel in boilers. Its use as fuel produces huge amounts of silica-rich rice husk ash (RHA). This paper aims at providing an overall assessment of environmental impacts associated with the extraction of silica from RHAa process developed by our study group. The functional unit used in this study is production of 100kg of silica. The analysis included the extraction and transportation of other raw materials; RHA was assumed to be processed at the site. The study was conducted in accordance with the international ISO 14040 procedural framework. LCA is performed using GaBi Education software, and five midpoint indicators are chosen to assess the environmental impacts of silica extraction. The overall climate change (CC) of the extraction process is 7.26kg CO2 equivalent per kg of silica produced. A high contribution of calcination to CC is attributed to the use of electricity. The comprehensive environmental impacts of silica-rich RHA resulting from processing of RHA and improvement options to achieve sustainable production are presented. The negative impacts that can be avoided during silica extraction are also discussed. It is observed that calcination is a major contributor to the overall environmental indicators. The work also stresses on the use of renewable energy for electricity generation, which would help in decreasing the overall greenhouse gas emissions during extraction while ensuring waste utilization.
Keywords: Environmental impacts; Life cycle assessment; Rice husk ash; silica